The Quiet Counter-Revolution: Structural Control of Syngenetic Deposits - Nelson, JoAnne (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary Syngenetic massive sulphide deposits, defined as sea-floor accumulations of sulphide minerals along with their enclosing strata, produce most of Canada's lead and zinc, as well as significant amounts of copper and precious metals. Their definition as a class has come about during the last 40 years, at the expense of earlier models that defined them as structurally controlled replacement deposits. This re-definition led to a shift in emphasis to observed stratigraphie as opposed to structural features; in some cases, syngenetic advocates even dismissed local structural control as coincidental. Two recent research development shave enhanced our understanding of syngenetic deposits in deformed belts. First is the volume and quality of data now available on modern sea-floor hydrothermal systems in a wide variety of tectonic settings, from the Middle Valley of the Juande Fuca Ridge to the back-arc basins of the western Pacific, and in particular Kuroko (rifted arc) analogues, which previously were poorly studied compared tomid-ocean ridge and continental rift examples. Second is the concept and study of inverted basins: the mechanisms by which normal fault-bounded basins are deformed during later crustal compression, and the peculiar structural geometries that result. Present investigations of syngenetic deposits now evaluate equally their stratigraphic setting — the "ore horizon" concept — and the primary and reactivated structures that controlled their origins.